2013
DOI: 10.3998/ark.5550190.0014.305
|View full text |Cite
|
Sign up to set email alerts
|

An efficient approach to the cyclotrimerisation of alkynes: solvent-free synthesis of 1,3,5-trisubstituted benzenes using p-toluenesulfonic acid monohydrate

Abstract: An environmentally friendly, efficient method for transforming alkynes into substituted benzenes catalyzed by p-toluenesulfonic acid monohydrate (p-TsOH·H 2 O) under solvent-free conditions has been developed, which conforms to the principles of "green" chemistry and overcomes the shortcomings of previous methods for the synthesis of substituted benzenes. The reaction is quite general and provides good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The reaction occurred slowly when the operating current was decreased to 5 mA (entry 15), whereas increasing it to 15 mA led to a slightly lower yield in a shorter reaction time (entry 16). To check the reaction for the generation of a ketone intermediate, 4-methoxyacetophenone was used instead of alkyne 1a , but did not undergo cyclotrimerization under the standard conditions (entry 17) …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction occurred slowly when the operating current was decreased to 5 mA (entry 15), whereas increasing it to 15 mA led to a slightly lower yield in a shorter reaction time (entry 16). To check the reaction for the generation of a ketone intermediate, 4-methoxyacetophenone was used instead of alkyne 1a , but did not undergo cyclotrimerization under the standard conditions (entry 17) …”
Section: Results and Discussionmentioning
confidence: 99%
“…To check the reaction for the generation of a ketone intermediate, 4-methoxyacetophenone was used instead of alkyne 1a, but did not undergo cyclotrimerization under the standard conditions (entry 17). 18 After optimizing the 1,3,5-cyclotrimerization process, we turned our attention to improving the yield and regioselectivity for the 1,2,4-regioisomer. Various mixed solvent systems and solvent ratios were surveyed, but no significant improvement in either the selectivity or yield of 1,2,4-regioisomer 3a was found (entries 18 and 19, and Table S1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In Pan's work, the mechanism of the PTSA-catalyzed cyclotrimerization of arylalkynes involved the formation of the intermediate of acetophenone, which then yielded 1,3,5-triphenylbenzene. 37 The results from the 1 H and 13 C NMR spectra of hb-P1a also demonstrated that the terminal groups of hb-PAs include acetyl groups (Fig. 2 and 3).…”
Section: Structural Characterizationmentioning
confidence: 75%
“…Pan and coworkers reported a solvent-free p-toluenesulfonic acid monohydrate ( p-TsOH•H 2 O, PTSA)-catalyzed cyclotrimerization of trimethylsilyl-protected internal alkynes for the regiospecific synthesis of 1,3,5-trisubstituted benzenes. 37 To our knowledge, there is no report on the preparation of HBPs through the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal-catalyzed [2 + 2 + 2] cycloaddition serves as a powerful and useful method to access aromatic carbo- and heterocycles in a single step . Despite the large number of metal complexes such as cobalt, nickel, rhodium, iridium, and ruthenium used for such transformations in organic solvent, the search for the development of more environmentally friendly solventless [2 + 2 + 2] cycloadditions has been scarcely explored …”
mentioning
confidence: 99%